A Case-Report of Drug-Induced Mixed Liver Injury Resulting From Cefepime Exposure. (February 2023) - Malhotra, Kyle; Fazylov, Roman; Friedman-Jakubovics, Michelle
A 99-year-old African-American male presented to the hospital with severe sepsis secondary to a urinary tract infection. Upon initial presentation he was tachycardic, hypotensive and had leukocytosis. While he had signs of acute kidney injury, no signs of acute liver injury were present with his alanine transferase (ALT) and amino transferase (AST) levels measuring at 22 and 44 U/L, respectively. During the treatment course the patient began to show signs of clinical improvement. Despite this, his ALT and AST began to increase on day 2 of treatment and reached their peak of 210 and 239 U/L on day 4. Cefepime-induced liver injury was suspected and cefepime was discontinued. Upon cefepime discontinuation, liver enzymes downtrended and gradually returned to normal. No other likely medication causes of liver injury could be identified and alternative medical causes were ruled out. The lack of an alternative cause and the temporal relationship of cefepime use to hepatic dysfunction support the diagnosis of cefepime-induced liver injury. The patient's Roussel Uclaf Causality Assessment Methods score was 7, indicating this was a possible case of cefepime-induced liver injury, and the Naranjo Nomogram score was 5 indicating this was a probable case of cefepime-induced liver injury. While cefepime-induced liver injury is rare, clinicians should be cognizant of the potential for this adverse effect if liver enzyme elevation is detected during cefepime therapy and other common causes have been ruled out.